2019
DOI: 10.26911/jepublichealth.2019.04.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Effect of Village on the Risk of Pneumonia in Children Under Five in Magetan, East Java

Abstract: Background: Pneumonia is a major cause of illness and death in children under five worldwide. Studies into the contextual effect of village are lacking in Indonesia. This study aimed to determine contextual effect of village on the risk of pneumonia in children under five in Magetan, East Java. Subjects and Method: This was a case control study conducted in Magetan, East Java, from October 2018 to December 2018. A sample of 225 children under five from 25 villages was selected by fixed disease sampling. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(22 reference statements)
2
2
0
Order By: Relevance
“…This study is in line with a study conducted by Mustikarini et al (2019) that children under five whose family members were smokers had a 1.39 risk of experiencing pneumonia compared to children under five whose family members were not smokers (b=1.39; 95% CI=0.46 to 2.32; p=0.003). Alnur et al (2017), also stated that children under five years who had family members as smokers had a 2.35 times risk of having pneumonia compared to children under five years whose family members were not smokers (aOR=2.35; 95% CI= 1.15 to 4.79; p=0.019).…”
Section: Discussionsupporting
confidence: 91%
“…This study is in line with a study conducted by Mustikarini et al (2019) that children under five whose family members were smokers had a 1.39 risk of experiencing pneumonia compared to children under five whose family members were not smokers (b=1.39; 95% CI=0.46 to 2.32; p=0.003). Alnur et al (2017), also stated that children under five years who had family members as smokers had a 2.35 times risk of having pneumonia compared to children under five years whose family members were not smokers (aOR=2.35; 95% CI= 1.15 to 4.79; p=0.019).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding micronutrient supplementation, our study indicated that children who had not received vitamin A in the six months prior to data collection had a higher risk of developing pneumonia than children who had received vitamin A. Our study is in line with studies done in other parts of Ethiopia [ 8 , 40 ] Rwanda [ 41 ] and Java [ 42 ]. The role of vitamin A is still an essential micro-nutrient intervention in the growth and development of respiratory epithelial cells and lung tissue and improving a good immunity against acute respiratory infections including pneumonia [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…Children under five exposed to cooking fuel smoke have a risk of 1.43 times higher than not exposed to cooking fuel smoke (b = 1.46; 95% CI = 0.34 to 2.51; p = 0.010). Mustikarani et al (2019) stated that children under five who were exposed to smoke from cooking fuel were 1.51 times more likely to increase the incidence of pneumonia compared to infants who were not exposed to cooking fuel. Yunita et al (2017) stated that children under five who lived in homes which were exposed to smoke from household materials tend to have a greater risk of pneumonia by 5 times than children under five who lived in homes that were not exposed to household smoke.…”
Section: The Effect Of Healthy Behavior On Pneumoniamentioning
confidence: 99%